22+54x=-20*60x

Simple and best practice solution for 22+54x=-20*60x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 22+54x=-20*60x equation:



22+54x=-20*60x
We move all terms to the left:
22+54x-(-20*60x)=0
We get rid of parentheses
54x+20*60x+22=0
Wy multiply elements
54x+1200x+22=0
We add all the numbers together, and all the variables
1254x+22=0
We move all terms containing x to the left, all other terms to the right
1254x=-22
x=-22/1254
x=-1/57

See similar equations:

| -6(-7d-7)=-7(-6d-6) | | 8.27–3x=3x+27 | | 2w=15w-1 | | x+74+x+41=95 | | -8=-(4r-16)-8r | | 1/2(8+4x)=2x+6 | | 15x=12(x+3) | | 120=4(9)(3)+2(3)h | | ∣4c5+6∣∣∣−6=−5. | | 4x-6+8=x+3 | | 154-8x=9x+51 | | 30-12=3x | | 5(2x-3)+2x=2x+29-4 | | -6,5k=12 | | 4y+3+3y+4=9y-3 | | 5x+70+2x=42 | | (5x-8)96=540 | | 3=x7 | | 15-2/3x=21 | | 2(3a-6)=27-3a | | 30+25+5k=100 | | 15t=120,t=8 | | 4x/12=38 | | x.x^2=49 | | 4x-3=-4x+9 | | 49x^2+196=0 | | -6-5(-5-5x)=-25+3x | | -180=-18x | | m/2+1=-9 | | 7x-10=7x-19 | | 2(v+6)=14 | | 2=3v+14 |

Equations solver categories